2019
DOI: 10.21495/71-0-307
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Ballistic Resistance of Thermoplastic Laminate Under 9 X 19 Mm Parabellum Ammunition

Abstract: This paper presents the examination of laminates on a thermoplastic polypropylene (PP) matrix.A preliminary homogenization of the system was performed using a scanning electron microscope (SEM). Numerical simulations were carried out and the energy dissipation of 9x19 mm Parabellum with a velocity of 360 m/s ± 10 m/s was analyzed. The results of the simulation were compared to real samples after their overshot in the ballistic test. The aim of the study was to determine the ballistic limit of material systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The use of simplified simulation methods is extremely important from the point of view of the complexity and computational cost of numerical models. In a previous paper, the authors presented the possibility of using homogenization at the volume level of the entire composite level, layer and fabric/matrix layer, using volumetric elements, and the results showed that, the layer-based modeling works best, but the possibility of homogenization at the level of layers consisting of non-Newtonian fluid has not been tested so far [41]. In addition, an important aspect to which the authors have devoted attention is the limitation of injuries that may occur during dynamic deflections during the shelling of fabric composites.…”
Section: Introductionmentioning
confidence: 99%
“…The use of simplified simulation methods is extremely important from the point of view of the complexity and computational cost of numerical models. In a previous paper, the authors presented the possibility of using homogenization at the volume level of the entire composite level, layer and fabric/matrix layer, using volumetric elements, and the results showed that, the layer-based modeling works best, but the possibility of homogenization at the level of layers consisting of non-Newtonian fluid has not been tested so far [41]. In addition, an important aspect to which the authors have devoted attention is the limitation of injuries that may occur during dynamic deflections during the shelling of fabric composites.…”
Section: Introductionmentioning
confidence: 99%